The daily Drucker : 366 days of insight and motivation for getting the right things done - Drucker, Peter F. (Peter Ferdinand), 1909-2005.; Maciariello, Joseph A. (New York : HarperBusiness, 2004)
Revered management thinker Peter F. Drucker is our trusted guide in this thoughtful, day-by-day companion that offers his penetrating and practical wisdom. Amid the multiple pressures of our daily work lives, The Daily Drucker provides the inspiration and advice to meet the many challenges we face. With his trademark clarity, vision, and humanity, Drucker sets out his ideas on a broad swath of key topics, from time management, to innovation, to outsourcing, providing useful insights for each day of the year. These 366 daily readings have been harvested from Drucker's lifetime of work. At the bottom of each page, the reader will find an action point that spells out exactly how to put Drucker's ideas into practice. It is as if the wisest and most action-oriented management consultant in the world is in the room, offering his timeless gems of advice. The Daily Drucker is for anyone who seeks to understand and put to use Drucker's powerful words and ideas.
Includes bibliographical (p. 399-408) references.
1
Keywords: Management